Trapped in a Glass Bell Jar: Neural Correlates of Depersonalization and Derealization in Subjects at Clinical High-Risk of Psychosis and Depersonalization–Derealization Disorder - Büetiger, Jessica R.; Hubl, Daniela; Kupferschmid, Stephan; Schultze-Lutter, Frauke; Schimmelmann, Benno G.; Federspiel, Andrea; Hauf, Martinus; Walther, Sebastian; Kaess, Michael; Michel, Chantal; Kindler, Jochen (Frontiers in Psychiatry, 2020)
Background: Depersonalization (DP) and derealization (DR) are symptoms of a disruption of perceptual integration leading to an altered quality of subjective experiences such as feelings of unreality and detachment from the self (DP) or the surroundings (DR). Both DP and DR often occur in concert with other symptoms, for example in subjects at clinical high-risk (CHR) for psychosis, but also appear isolated in the form of DP/DR disorder. Despite evidence that DP/DR causes immense distress, little is known about their neurobiological underpinnings. Therefore, we investigated the neural correlates of DP/DR using pseudo-continuous arterial spin labeling MRI. Methods: We evaluated the frequency of DP/DR symptoms in a clinical sample (N=217) of help-seeking individuals from the Early Detection and Intervention Centre for Mental Crisis (CHR, n=97; clinical controls (CC), n=91; and first-episode psychosis (FEP), n=29). Further, in a subsample of those CHR subjects who underwent MRI, we investigated the resting-state regional cerebral blood flow (rCBF). Here, individuals with (n=21) and without (n=23) DP/DR were contrasted. Finally, rCBF was measured in a small independent second sample of patients with DP/DR disorder (n=6) and healthy controls (HC, n=6). Results: In the complete clinical sample, significantly higher frequency of DP/DR were found in CHR compared to CC (50.5% vs. 16.5%; X2(2)=24.218, p≤0.001, Cramer's V=0.359) as well as in FEP compared to CC (37.9% vs. 16.5%; X2(2)=5.960, p=0.015, Cramer's V=0.223). In MRI, significantly lower rCBF was detected in the left orbitofrontal cortex in CHR with vs. without DP/DR (x/y/z=-16/42/-22, p<0.05, FWE corrected). In patients with DP/DR disorder, significantly higher rCBF was detected in the left caudate nucleus (x/y/z=-18/-32/18, p<0.05) compared to HC. Conclusions: This study shows that DP/DR symptoms are frequently found in CHR subjects. Investigating two separate DP/DR populations with an identical neuroimaging technique, our study also indicates that there may be divergent pathophysiological mechanisms - decreased neuronal activity in the orbitofrontal cortex, but increased activity within the caudate nucleus - leading to a final common pathway with similar psychopathological symptoms. This suggests that both top-down (orbitofrontal cortex) and bottom-up (caudate nucleus) mechanisms could contribute to the emergence of DP/DR.